Evaluasi Implemetasi Pendidikan Karakter Melalui Kegiatan Ekstrakurikuler: Systematic Literature Review - Ambrosius Tode Peya Nia Do; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
Character education is an important component in the implementation of education. Character education aims to develop students into individuals who are noble and virtuous. In this context, extracurricular activities become one of the effective means to develop character values outside the academic or formal curriculum. This article aims to evaluate the implementation of character education through extracurricular activities using the Systematic Literature Review (SLR) approach. The SLR method was used to identify, analyze, and synthesize relevant literature within the last six years. The results of this review show that extracurricular activities are following the standards set to support the implementation of character values. The findings indicate that extracurricular activities have great potential in shaping students' character such as independence, cooperation, responsibility, and leadership. This can be realized if implemented with great awareness and evaluated with appropriate procedures. This article provides practical recommendations for more effective implementation in the future.